PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS NEARPOD PADA TEMA 6 SUBTEMA PERUBAHAN ENERGI KELAS III MI ROUDLOTUL MUSTASHLIHIN SUKODONO - Muhammad Assegaf Baalwi; Ulvi Aulia (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
This study aims to explain the development process and feasibility of interactive multimedia-based learning media using the Nearpod application on energy theme 6 and its changes in the energy change subtheme 1 for class III MI Roudlotul Mustashlihin Sukodono. The method used in this study is a development research method with the ADDIE development model developed by Dick and Carry. In the development carried out, researchers carried out three stages, namely (1) Analysis (analysis) (2) Design (design) and (3) Development (development). The development of this learning media produces interactive learning media using the Nearpod application for class III SD/MI students. The developed media has been validated by two validators with the results: (1) material expert validation obtained a score of 45 with a percentage value of 93.5% which is categorized as